Cost-effectiveness of simulation-based team training in obstetric emergencies (TOSTI study). (September 2017) - van de Ven, J.; van Baaren, G.J.; Fransen, A.F.; van Runnard Heimel, P.J.; Mol, B.W.; Oei, S.G.
Abstract: Objective: Team training is frequently applied in obstetrics. We aimed to evaluate the cost-effectiveness of obstetric multi-professional team training in a medical simulation centre. Study design: We performed a model-based cost-effectiveness analysis to evaluate four strategies for obstetric team training from a hospital perspective (no training, training without on-site repetition and training with 6 month or 3–6-9 month repetition). Data were retrieved from the TOSTI study, a randomised controlled trial evaluating team training in a medical simulation centre. We calculated the incremental cost-effectiveness ratio (ICER), which represent the costs to prevent the adverse outcome, here (1) the composite outcome of obstetric complications and (2) specifically neonatal trauma due to shoulder dystocia. Results: Mean costs of a one-day multi-professional team training in a medical simulation centre were €25, 546 to train all personnel of one hospital. A single training in a medical simulation centre was less effective and more costly compared to strategies that included repetition training. Compared to no training, the ICERs to prevent a composite outcome of obstetric complications were €3432 for a single repetition training course on-site six months after the initial training and €5115 for a three monthly repetition training course on-site after the initial training during one year. When we considered neonatal trauma due to shoulder dystocia, a three monthly repetition training course on-site after the initial training had an ICER of €22, 878. Conclusion: Multi-professional team training in a medical simulation centre is cost-effective in a scenario where repetition training sessions are performed on-site.